2013
DOI: 10.1155/2013/194389
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Extended Interval Dosing Aminoglycosides in the Morbidly Obese Population

Abstract: Aminoglycoside dosing has been studied in the obese population, typically recommending an adjusted weight utilizing a 40% dosing weight correction factor (IBW + 0.4 × (TBW–IBW)). These studies included limited numbers of morbidly obese patients and were not done in the era of extended interval aminoglycoside dosing. Here, we report a retrospective evaluation of morbidly obese patients receiving gentamicin or tobramycin at our hospital. The objective of this study was to evaluate the accuracy of the commonly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In obese children, the Vd of aminoglycosides (adjusted to TBW in L/kg) is reduced and t½ remains unchanged . For traditional dosing of aminoglycosides, it is typically recommended to use the TBW or AdjBW (with a maximum dose), as opposed to LBW or IBW, for the loading doses in obese adults and children because it is critical to achieve high initial peak concentrations of ~8 µg/ml for tobramycin and gentamicin to maximize bactericidal activity (Tables and ) . Therapeutic drug monitoring after the initial dose is vital to prevent high trough concentrations that may lead to cumulative nephrotoxicity and ototoxicity …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In obese children, the Vd of aminoglycosides (adjusted to TBW in L/kg) is reduced and t½ remains unchanged . For traditional dosing of aminoglycosides, it is typically recommended to use the TBW or AdjBW (with a maximum dose), as opposed to LBW or IBW, for the loading doses in obese adults and children because it is critical to achieve high initial peak concentrations of ~8 µg/ml for tobramycin and gentamicin to maximize bactericidal activity (Tables and ) . Therapeutic drug monitoring after the initial dose is vital to prevent high trough concentrations that may lead to cumulative nephrotoxicity and ototoxicity …”
Section: Methodsmentioning
confidence: 99%
“…A third study of obese adults examining once/day (extended) dosing of gentamicin found that 71% of subjects were within the desired therapeutic concentration range (less than 2 µg/ml) 16 hours after initial dose when dosed at 5–7 mg/kg every 24 hours by AdjBW …”
Section: Methodsmentioning
confidence: 99%
“…Serum drug concentration was therapeutic in 71%, supratherapeutic in 13%, and subtherapeutic in 16% [18]. The only variable that correlated with supratherapeutic levels was older age ( P  = 0.04) [18]. Another study demonstrated that estimated lean body weight (LBW) (Table 1) was better than TBW and IBW to predict aminoglycoside Vd, and showed an improved prediction of aminoglycoside clearance using equations that estimate GFR rather than CL cr (Table 1) [19].…”
Section: Antibiotic Dosing and Delivery In Obese Patientsmentioning
confidence: 99%
“…Adjusted body weight (ABW) is usually recommended for aminoglycosides dosing ( Table 1 ). One study evaluated ABW for weight-based dosing in 31 morbidly obese patients who received gentamicin or tobramycin 5–7 mg/kg every 24 h [18] . Serum drug concentration was therapeutic in 71%, supratherapeutic in 13%, and subtherapeutic in 16% [18] .…”
Section: Antibiotic Dosing and Delivery In Obese Patientsmentioning
confidence: 99%
See 1 more Smart Citation